Optimalisasi Pembelajaran Terpadu Melalui Model Irisan (The Shared Model) di Kelas V: Studi Kasus SD Negeri 1 Bancar dan SD Negeri 2 Bancar - rakhmat, rakhmat; Putra, Ade Ima; Jiamelatun, Jiamelatun; Prastiwi, Destiana Vidya; Hermawan, M. Ajib (JURNAL LENTERA [PENDIDIKAN PUSAT PENELITIAN LPPM UM METRO], 2026)
This study aims to optimize integrated learning through the Shared Model (Model Irisan) in fifth-grade students at SD Negeri 1 Bancar and SD Negeri 2 Bancar. The research was motivated by the lack of integration among subjects, low student engagement, and limited conceptual understanding in elementary classrooms. A qualitative case study approach was employed, involving teachers and 30 students as research subjects. Data were collected through observation, interviews, documentation, and questionnaires, then analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that the implementation of the Shared Model significantly enhances student engagement, conceptual understanding, and higher-order thinking skills. Students showed increased participation in discussions, improved collaboration in group activities, and better ability to connect concepts across subjects. Furthermore, contextual learning activities enabled students to relate academic content to real-life experiences, making learning more meaningful. Despite challenges such as extended planning time and the need for teacher readiness, the model proved effective in creating an interactive and integrated learning environment. In conclusion, the Shared Model is a promising approach for improving the quality of integrated learning in elementary schools.